Pengaruh Akad Murahabah terhadap Profitabilitas Bank Umum Syariah di Indonesia - Uswatun Hasanah; Rodiah Harahap (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study examines the impact of murabahah contracts on profitability in the Islamic banking sector in Indonesia, especially in Islamic Commercial Banks. In this study, Return on Assets is used as the main indicator to measure the level of bank profitability. Multiple linear regression is used to empirically test the relationship between murabahah financing and Return on Assets. The results of the study indicate that murabahah financing has a significant and positive effect on Return on Assets. This indicates that the higher the level of murabahah financing disbursed, the greater the increase in profitability of Islamic Commercial Banks. This finding strengthens the evidence in previous literature regarding the importance of the role of Islamic financing product strategies in improving the results of Islamic banking financial institutions. As a result, this study emphasizes the importance of optimizing financing strategies based on murabahah contracts as a major component in the product portfolio of Islamic Commercial Banks. Therefore, to improve competitiveness, efficiency, and create sustainable financial stability in the national Islamic banking system, it is necessary to develop and implement more effective and efficient murabahah contracts by all Islamic banking institutions in Indonesia and work well by all Islamic banking institutions in Indonesia.